Analisis kesenjangan nafkah pasca perceraian antara praktik dan teori - Azmi, Muhammad Ulul (Maliki Interdisciplinary Journal, 2025)
Post-divorce maintenance is a legal consequence arising from a divorce. Regulations regarding post-divorce maintenance have been widely explained in the Law and the Qur'an. Unfortunately, existing regulations or theories are often not in line with the practices that live in the community. This analysis aims to identify the gap that exists between theory and practice in terms of post-divorce maintenance fulfillment. This research will try to examine the factors that cause the gap between theory and practice regarding post-divorce maintenance. By understanding each of the existing gaps, it is hoped that this paper can provide more effective recommendations or solutions to protect the rights arising from divorce that have post-divorce maintenance implications